Protective mechanism and clinical application of SGLT2 inhibitors in patients with type 2 diabetes mellitus complicated with abnormal liver function - Zhao, Yunhui (International Journal of Public Health and Medical Research, 2024)
Type 2 diabetes (T2DM) patients with abnormal liver function will further aggravate the complexity of the disease and affect the quality of life of patients. Sodium-glucose cotransporter protein 2 (SGLT2) inhibitors are novel hypoglycemic agents that may produce hepatoprotective effects in patients with T2DM combined with hepatic function abnormalities by improving hyperglycemic toxicity, regulating lipid metabolism, decreasing visceral adiposity, anti-inflammatory, antioxidant and other possible mechanisms. However, the exact mechanism has not been clarified and further studies are still needed. In this article, we reviewed the possible mechanisms of hepatoprotective effects of SGLT2i on patients with T2DM combined with abnormal liver function and the progress of clinical application, in order to providing reference for the rational application of SGLT2i.